Static Buckling and Free Vibration Analysis of Aligned CNTs Reinforced Composite Plates - Dinh Nguyen, Pham; Ha, Do Thi Thu; Manh Tuan, Duong (VNU Journal of Science: Mathematics - Physics, 2023)
This work introduces an analysis of the nonlinear buckling and free vibration behavior of polymer plates reinforced with aligned carbon nanotubes using Reddy's third-order shear deformation plate theory and incorporating Theodore von Kármán's geometric nonlinearity. The polymer plates were enhanced with single-walled carbon nanotubes assumed to exhibit either uniform distribution or functionally graded distribution across the thickness. The equations of motion were established through Hamilton’s principle and then solved by the Galerkin method and Airy’s stress function for the composite plates with fully simply supported edges. The investigation focused on assessing the effects of carbon nanotube distribution, volume fraction, and geometrical parameters on the buckling load and fundamental frequency parameters of composite plates through numerical results.